Immigration and the Slope of the Labor Demand Curve: The Role of Firm Heterogeneity in a Model of Regional Labor Markets - Andrea Ariu; Tobias Müller; Tuan Nguyen (Center for Economic Studies and ifo Institute (CESifo), 2023)
In this paper, we provide new explanations for the puzzling findings in the literature that migrants do not decrease natives' wages, and that skilled immigration can actually increase them. We develop a model with regional labor markets and heterogeneous firms in which workers of different skill levels are imperfect substitutes, but for a given skill level, natives and migrants are perfect substitutes within a firm. In this setting, a skilled labor supply shock due to immigration has two consequences. First, it induces skill-intensive firms and skill-abundant regions to expand. These across-firm and across-region reallocations reduce the within-firm and within-region substitution between skilled and unskilled workers, thus limiting relative wage adjustments. Second, the average native's wage can be partially sheltered from the negative effect of immigration depending on the geographical settlement patterns of immigrants. Both mechanisms make natives and migrants appear as imperfect substitutes at the aggregate level. Quantitatively, our simulations show that the negative impact of immigration on natives' wage is halved when the across-firm and across-region reallocation mechanisms are at work. Finally, both theory and simulations show that when these mechanisms are coupled with human-capital externalities that are skill-neutral at the firm level but skill-biased on aggregate, skilled immigration can increase absolute and relative skilled wages. Therefore, firm heterogeneity, local labor markets, and human-capital externalities are crucial for understanding the impact of immigration on natives' wages.
Keywords: F22; J61; J31; 330; immigration; firm heterogeneity; wages